Enhanced mechanical and thermal properties of poly (lactic acid)/bamboo fiber composites via surface modification. (June 2018) - Hu, Guang; Cai, Shenyang; Zhou, Yinghui; Zhang, Naiwen; Ren, Jie
Three different kinds of surface treatment procedures were used to modify the surface of bamboo fiber: alkali solution treatment (NaOH), alkali and silane coupling agent treatment (NaOH–KH550) and alkali and titanate coupling agent treatment (NaOH–NDZ201). Then the bamboo fiber reinforced poly (lactic acid) composites were prepared by Haake Mixer and characterized by FTIR spectroscopy, mechanics performance tests, differential scanning calorimetry analysis, thermogravimetric analysis, Vicat softening temperature, X-ray diffraction analysis and scanning electron microscopy. The results showed that incorporation of surface-treated bamboo fiber obviously improved the mechanical properties of poly (lactic acid). Especially, the tensile, flexural and impact strengths of poly (lactic acid) containing NaOH–NDZ201-treated bamboo fiber were higher than those of poly (lactic acid) containing NaOH and NaOH–KH550-treated bamboo fiber. Moreover, the NaOH–NDZ201-treated bamboo fiber also greatly enhanced the thermal stability of poly (lactic acid). The improvement of mechanical strengths and thermal stability of poly (lactic acid)/bamboo fiber composites might be due to the better interfacial adhesion between poly (lactic acid) and NaOH–NDZ201-treated bamboo fiber.